Efektivitas Same Day Passport Service dalam Pembuatan Paspor di Kantor Imigrasi Kelas I Tanjungpinang - Halisa Putri; Fitri Kurnianingsih; Jamhur Poti (Universitas 17 Agustus 1945, 2026)
Public services in the immigration sector are required to be faster and more responsive to the surge in public demand, including through the implementation of the Same Day Passport Service as a facility to expedite passport issuance. This study aims to analyze the effectiveness of the Same Day Passport Service at the Tanjungpinang Class I Immigration Office and to reveal the obstacles that hinder it. A qualitative approach with a descriptive design was used. Data was collected through in-depth interviews, observations, and document studies from immigration officials and service users. Data analysis referred to Sutrisno's service effectiveness indicators, namely program understanding, target accuracy, timeliness, goal achievement, and tangible changes. The results of the study indicate that the Same Day Passport Service has been effective overall, particularly in terms of timeliness, achievement of service objectives, and concrete changes in the quality of passport production. However, its effectiveness has not been maximized due to the public's limited understanding of service requirements and the accuracy of applicant targeting. This study emphasizes the urgency of increasing socialization, strengthening the applicant selection mechanism, optimizing resources, and support systems to improve the effectiveness of immigration services.